Inovasi Pemanfaatan Limbah Ampas Tahu Menjadi Kerupuk di Dusun Bunut Kidul Desa Asrikaton - Maulida Filailin Mubarokah; Syafaatur Rahmah; Siti Fatimah; Maulana Dhiyahul Haq (Jurnal Pengabdian Masyarakat, 2024)
Asrikaton Village to be precise in Bunut Kidul Hamlet is known for its various advanced SME products, one of the most loved is Mr. Abdurrahman's tofu product which has been established since 1984. This tofu factory is well known to the public and is recognized for its quality and taste. However, after observing that there is one obstacle that cannot be handled optimally, namely the utilization of waste from tofu dregs. To optimize the use of tofu dregs, we took the initiative to try to develop a tofu dregs cracker product. As for the method of writing this scientific article with qualitative research, the data source chosen by the researcher is Mr. Abdurrahman's tofu factory. Researchers collected data using field research techniques and interviews, namely by going directly to the tofu-making factory to find out the tofu-making process. Then, using analytical techniques, the researcher analyzed interviews with tofu factory owners related to problems related to the tofu factory business regarding the utilization of tofu dregs.